Polymorphism in PfMRP1 (Plasmodium falciparum multidrug resistance protein 1) Amino Acid 1466 associated with resistance to Sulfadoxine-Pyrimethamine treatment - Dahlstrom, Sabina (2018)
Sulfadoxine-pyrimethamine (SP) remains widely recommended for intermittent preventive treatment against Plasmodium falciparum malaria for pregnant women and infants in Africa. Resistance to SP is increasing and associated primarily with mutations in the P. falciparum dhfr (Pfdhfr) and Pfdhps genes. This study aimed to explore the hypothetical association of genetic alterations in the P. falciparum multidrug resistance protein gene (Pfmrp1) with the in vivo response to SP by detecting the selection of single nucleotide polymorphisms (SNPs) following standard single-dose treatment administered to children with acute uncomplicated P. falciparum malaria in Tanzania. We detected significant selection of parasites carrying the Pfmrp1 1466K allele in samples from children with recrudescent infections, with 12 (100%) of 12 such samples being positive for this allele, compared to 52 (67.5%) of 77 baseline samples (P=0.017), in parallel with the selection of the Pfdhfr Pfdhps quintuple mutant haplotype in cases of recrudescence (P=0.001). There was no association between the 1466K SNP and the Pfdhfr Pfdhps quintuple mutation, indicating independent selections. Our data point for the first time to a role for a P. falciparum multidrug resistance protein homologue in the antimalarial activity of SP. Moreover, they add to the growing evidence of the potential importance of Pfmrp1 in antimalarial drug resistance.